1992
DOI: 10.1111/j.1442-200x.1992.tb00963.x
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Psychosocial Factors in the Psychosomatic Symptoms of Adolescents in Okinawa

Abstract: High school students (N = 902) in Okinawa were asked to participate in a questionnaire survey which was designed to investigate the psychosocial factors in the psychosomatic symptoms of adolescents. The questionnaire focused on mental distress, perception of school and home environment and psychosomatic symptoms. The Japanese Edition Cornell Medical Index‐Health Questionnaire (JCMI) for evaluating emotional instability and the New TK Diagnostic Test for Parent‐Child Relationship were also utilized. Distress in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Students and workers who are overloaded sometimes develop a burnout syndrome, which involves the autonomic nervous system. 39 Previous studies reported that Japanese children with symptoms of OD have psychosocial problems including personality, 40 human relationship 41 and family problems. 42,43 In agreement with this, more than half of the children with OD have school refusal (phobia) and 30 -40% children with school refusal have OD.…”
Section: Aspect Of Psychosomatic Diseasementioning
confidence: 99%
“…Students and workers who are overloaded sometimes develop a burnout syndrome, which involves the autonomic nervous system. 39 Previous studies reported that Japanese children with symptoms of OD have psychosocial problems including personality, 40 human relationship 41 and family problems. 42,43 In agreement with this, more than half of the children with OD have school refusal (phobia) and 30 -40% children with school refusal have OD.…”
Section: Aspect Of Psychosomatic Diseasementioning
confidence: 99%
“…(In the West during the first half of the 20th century, anxiety states were often diagnosed as "neurocirculatory asthenia"; typical symptoms included palpitations, easily induced fatigue, and orthostatically induced dizziness [for a review, see 20].) The diagnosis of neurocirculatory asthenia was adopted in Japan, but with orthostatic dizziness as the central focus, and a new name given: orthostatic dysregulation [21][22][23][24][25][26]. It is a category used by Japanese health professionals and is well known by laypersons.…”
Section: Japanmentioning
confidence: 99%
“…The core concepts of neurocirculatory asthenia were borrowed into Japan, but with orthostatic dizziness made the central focus, and a new name given: orthostatic dysregulation (Abe, 1990;Honda, Nose, Yoshida, Tanimura, & Tanaka, 1977;Igarashi, 1971;Nakada, 1992;Nozawa et al, 1996Nozawa et al, , 1997Tanaka, Thulesius, Borres, Yamaguchi, & Mino, 1994;Torigoe et al, 2001). 9 In orthostatic dysregulation (Abe, 1990), the person has:…”
Section: The Centrality Of Orthostasis-induced Dizziness In Certain Asian Distress Syndromesmentioning
confidence: 99%